English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-03 11:15:51 · 5 answers · asked by matt h 1 in Science & Mathematics Mathematics

5 answers

y = 9 - x

Put x for y and y for x. Then solve for y

x = 9 - y
y = 9 - x

Final answer. The inverse is itself.

2006-12-03 11:21:03 · answer #1 · answered by ? 6 · 0 0

Function?

2006-12-04 09:41:46 · answer #2 · answered by Johnathan 2 · 0 0

the inverse means finding f(-x)
so, it becomes:

9 - (-x) = 9 + x

2006-12-03 11:23:45 · answer #3 · answered by mennor 2 · 0 1

f(x) = 9 - x = y
solve for x , we have : x = 9 - y
we can see that with a certain value of y, we can only have one value of y
so we conclude that y = g(x) = 9 - x is the inverse of itself ( because f(x) = g(x) = 9 - x )

2006-12-03 11:22:23 · answer #4 · answered by James Chan 4 · 0 0

f(x) = 9-x
y = 9-x
x = 9-y
-y=x-9
y = -x+9
f(x) = -x+9

2006-12-03 11:28:15 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers